Leisure-based reading and the place of e-books in everyday life - , Annika Hupfeld; Sellen, Abigail; O'Hara, Kenton; Rodden, Tom (Proceedings of INTERACT 2013, 2013)
With the proliferation of digital reading technologies and their underlying ecosystem, practices of reading are currently undergoing significant changes. Despite the currency of the topic, we find there is little empirical research on how people incorporate digital reading technologies into their existing leisure-based reading practices. In this paper, we explore the place of ereading for pleasure in daily life, and how it is co-evolving with practices surrounding printed books. We present a diary study with 16 readers tracking their behaviors and motivations surrounding e-book use. Our findings are relevant to designers of digital reading technologies in highlighting the values guiding people‟s choices and behaviors concerning e-book use.